PENGEMBANGAN POTENSI WISATA AIR DUSUN PANGANCRAAN SEBAGAI DESTINASI WISATA UNGGULAN PENGGERAK EKONOMI LOKAL - Rusliana, Nanang; Susilo, Ignatia Bintang Filia Dei; Paturochman, Iwan Ridwan; Kadarisman, Encang; Rudiana, Dedi (Universitas Sanata Dharma, 2024)
This community service program aimed to optimize the water tourism potential of Pangancraan Hamlet, Cijulang, Pangandaran as a driving force of the local economic growth. Despite its natural beauty, which is ideal for river tubing, the tourism sector remains underdeveloped due to limited promotion, uncoordinated tourism management, and declining community enthusiasm for managing tourism activities. Revitalization of the